Preservation of ripe mango chunks by hurdle technology - Rekha Raveendran R S (Department of Home Science, College of Agriculture, 2009)
Mango (Mangifera indica L.) is one of the most important tropical fruit crops and is often called as “King of fruits”. Although India is the second largest producer of fruits, the domestic fruit industry is fraught with the massive problem of wastage caused by the woefully inadequate post harvest facilities and other supportive infrastructure including cold chain.